Studies on Determination of Optimum Sowing Method of Prinsepia utilis Royle Seed in the Field - Bhagat, Sarjan; Singh, Ombir (Indian Forester, 1991)
A study was undertaken to determine the feasibility of direct sowing of Prinsepia utilis seed in the field. Three methods of sowIng viz., broadcast sowing, dibbling and line sowing were adopted. The results showed that line sowing was significantly better tban broadcast sowing in terms of germination percentage, seedling growth and seedling dry weight was also significantly superior to dibbling sowing In terms of seedling growtb and seedling dry weight.